Simulation of simple gas motion in a 2-D box using Java - 504913 Nurhazwani Zanuddin,ld1988-; Mohd. Nor Md. Yusof; Mohd. Asmu`i Mohd. Akil; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains (Fizik)) - Universiti Teknologi Malaysia, 2010